FIRM SPECIFIC FACTORS THAT DETERMINE INSURANCE COMPANIES’ PERFORMANCE IN ETHIOPIA - Mehari, Daniel; Aemiro, Tilahun (European Scientific Journal, ESJ, 2013)
ï»¿ï»¿The performance of any business firm not only plays the role to improve the market value of that specific firm but also leads towards the growth of the whole sector which ultimately leads towards the overall prosperity of the economy. Assessing the determinants of the performance of organizations has gained importance in the corporate finance literature; however, in the context of insurance sector, it has received little attention particularly in Ethiopia. Accordingly, this study investigated the impact of firm level characteristics (size, leverage, tangibility, Loss ratio (risk), growth in writing premium, liquidity and age) on performance of insurance companies in Ethiopia. Return on total assets (ROA) - a key indicator of insurance company’s performance- is used as dependent variable while age of company, size of the company, growth in writing premium, liquidity, leverage and loss ratio are independent variables. The sample includes 9 insurance companies over the period 2005-2010. The audited annual reports (Balance sheet and Profit/Loss account) of insurance companies were obtained from National Bank of Ethiopia (NBE) and insurance companiesâ€™ annual publication reports. The results of regression analysis reveal that insurersâ€™ size, tangibility and leverage are statistically significant and positively related with return on total asset; however, loss ratio (risk) is statistically significant and negatively related with ROA. Thus, insurersâ€™ size, Loss ratio (risk), tangibility and leverage are important determinants of performance of insurance companies in Ethiopia. But, growth in writing premium, insurersâ€™ age and liquidity have statistically insignificant relationship with ROA.